ANALISIS PENERIMAAN RETRIBUSI PARKIR TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN ENDE - Maria Imakulata Kota; Baltasar Taruma Djata (Program Studi Ekonomi Pembangunan Universitas Flores, 2021)
This study aims to determine the effectiveness, efficiency and contribution of parking fees in Ende Regency. The data collection method used in this research is quantitative because the data comes from the transportation office of Endedan district, DPPKAD, Ende Regency. The results of the data analysis show that (1) The trend of receiving parking fees in Ende district in 2012 to 2015 is negative. (2) The effectiveness of receiving parking fees in Ende district from 2012 to 2015 was ineffective due to the lack of discipline of the collectors. (3) The efficiency of receiving parking fees in Ende Regency in 2012 to 2015 is very efficient, because the efficiency achieved is below 100%. (4) The contribution of parking fee receipts to local revenue in Ende Regency in 2012 to 2013 has increased in 2013 to 2014 has decreased and from 2014 to 2015 has increased. The relationship of effectiveness, efficiency and contribution from 2012 to 2015 was very ineffective because the revenue from parking fees every year was not balanced and was unable to contribute to PAD